Analisis Sintaksis dan Semantis dalam Ragam Bahasa Indonesia Formal dan Nonformal - Agus Kusuma Wardana (Journal of Language Studies, 2025)
Language use is deeply rooted in its social context, where syntactic and semantic choices reflect both situational formality and communicative intent. This article explores how syntactic and semantic patterns differ between formal and nonformal varieties of Indonesian language, focusing on implications for language learning and teaching. The study aims to investigate how sociolinguistic approaches—particularly those emphasizing communicative competence—can be integrated into secondary school language instruction to enhance students’ pragmatic and sociocultural awareness. Using a qualitative descriptive method and literature review approach, data were collected from scholarly sources such as journals, books, and conference proceedings available through platforms like Google Scholar. Thematic content analysis was used to identify patterns and key findings. The results indicate that practical classroom strategies—such as authentic discourse analysis, role-playing, and language variation discussions—can significantly improve students’ understanding of language register, politeness strategies, and contextual appropriateness. This, in turn, enhances their pragmatic competence and social adaptability. The paper highlights the value of sociolinguistic frameworks as a bridge between linguistic knowledge and real-world communication skills, calling for curriculum reforms and teacher training to better address these dimensions.